New and Interesting Diatoms (Bacillariophyta) from Blue Lake Warm Springs, Tooele County, Utah - Graeff, C. L.; Kociolek, J.p.; Rushforth, S.r. (Phytotaxa, 2013)
Blue Lake Warm Springs is a system of brackish lakes and marshes in western Utah, USA with a unique diatom flora that has been previously documented. Here we reexamine select taxa in greater detail, erecting two new genera and six new species from this system, and describing two additional species not observed in prior studies of the Blue Lake flora. Naviculonema stagnora gen. nov., sp. nov. and Williamsella angusta gen. nov., sp. nov are a new naviculoid genus and new pennate diatom genus lacking a raphe, respectively. Other new species of diatoms from Blue Lake Warm Springs, representing a broad range of diatom diversity, are Cyclotella utahensis sp. nov., Ulnaria tooelensis sp. nov., Pseudostaurosira moralesii sp. nov., Envekadea vanlandinghamii sp. nov., Mastogloia variabilis sp. nov., and Lunella excentrica sp. nov. The report of Envekadea is the first of the genus from inland USA waters, and the report of Lunella is the first from the USA. In addition to describing new taxa in this study, we also closely examine two known taxa, Fallacia pseudolitoricola and Nitzschia vitrea, with scanning electron microscopy, in order to better understand their morphology and biogeography. Presence of euryhaline or salt tolerant taxa in this inland ecosystem may be due to introductions by humans, either via escaped aquaculture species or transport by recreational SCUBA diving.